2023
DOI: 10.1111/jdv.19220
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma in children: A systematic review and individual patient meta‐analysis

Abstract: The current evidence on paediatric melanoma is heterogeneous, especially regarding the prognosis of different histological subtypes. We sought to systematically review the evidence on paediatric melanoma, highlighting the major sources of heterogeneity and focusing on available data on single patients. A systematic search was performed from 1948 to 25 January 2021. Only studies reporting at least one case of cutaneous melanoma in patients aged ≤18 years were included. Unknown primary and uncertain malignant me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 283 publications
0
3
0
Order By: Relevance
“…Distinct from melanoma in adults, spitzoid melanoma is one of the most common histologic subtypes in pediatric patients with melanoma. Interestingly, a recent meta-analysis including 1002 patients with melanoma have demonstrated that spitzoid melanoma with higher occurrence in children younger than 10 years harbors higher Breslow thickness and more propensity to nodal metastasis than non-spitzoid melanomas, but shows a more indolent biological behavior and a better prognosis [ 7 ]. Additionally, nevus-associated melanoma is more frequently observed in children than in adults, as a higher number of pediatric melanomas are associated with congenital nevi in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct from melanoma in adults, spitzoid melanoma is one of the most common histologic subtypes in pediatric patients with melanoma. Interestingly, a recent meta-analysis including 1002 patients with melanoma have demonstrated that spitzoid melanoma with higher occurrence in children younger than 10 years harbors higher Breslow thickness and more propensity to nodal metastasis than non-spitzoid melanomas, but shows a more indolent biological behavior and a better prognosis [ 7 ]. Additionally, nevus-associated melanoma is more frequently observed in children than in adults, as a higher number of pediatric melanomas are associated with congenital nevi in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation of any nevus is rare; however, a quarter of all superficial spreading melanomas (SSM) originate from a pre-existing AMN (Pampena et al 2023). In contrast, multiple medium to giant CMN are associated with significantly increased risk for prepubertal melanoma, particularly nodular (NM) but also extracutaneous, in direct proportion to the size and number of congenital lesions.…”
Section: To the Editormentioning
confidence: 99%
“…However, the incidence increases significantly in adolescents and reaches about 10 times the incidence of children in the age group of 15–19 years (Ferrari et al., 2019; Strouse et al., 2005). Most pediatric melanomas have a rather benign course, but there are also fatal outcomes in this age group (Pampena et al., 2023). The prognosis differs significantly between the subtypes of pediatric melanoma.…”
Section: Introductionmentioning
confidence: 99%